Associations between social eating contexts and affective states in adolescents: the EHDLA study - Montenegro-Espinosa, José Adrián; Quiroz-Cárdenas, Fiorella; Yañéz-Sepúlveda, Rodrigo; Gutiérrez-Espinoza, Héctor; Olivares-Arancibia, Jorge; López-Gil, José Francisco (Frontiers in Nutrition, 2025)
IntroductionPositive and negative affect (PA and NA) are crucial dimensions of emotional experience, that could influence psychological wellbeing in adolescents. Social interactions, particularly around mealtimes, may play a relevant role in adolescent development and wellbeing. This study investigates the associations of family meals and social eating behavior (SEB) with PA and NA in Spanish adolescents.MethodsThis cross-sectional study included 637 adolescents (43% boys) aged 12–17 years from the Valle de Ricote, Region of Murcia, Spain. PA and NA were measured using the Spanish version of the Positive and Negative Affect Schedule for Children (PANAS-C10). Family meal frequency was assessed by asking participants how many times they ate with most household members in the previous week. SEB was evaluated with a three-item self-report instrument capturing the frequency and importance of eating with others. Robust generalized linear models (Gaussian family, identity link; “lmrob” function, “robustbase” package, R) were used to analyze the associations between family meals/SEB and PA and NA, adjusting for age, sex, socioeconomic status, physical activity, sedentary behavior, sleep duration, body mass index, and energy intake.ResultsThe median weekly family meals were 14.0 [interquartile range (IQR) 10.0, 16.0], SEB score was 10.0 (IQR 9.0, 11.0), PA score was 19.0 (IQR 15.0, 22.0), and NA score was 8.0 (IQR 6.0, 13.0). Higher SEB scores were related to greater PA [unstandardized beta coefficient (B) = 0.44, 95% confidence interval (CI) 0.20 to 0.69, p < 0.001]. A borderline association was found between family meals and PA (B = 0.09, 95% CI −0.001 to 0.18, p = 0.054). Conversely, both higher SEB scores (B = −0.21, 95% CI −0.40 to −0.01, p = 0.038) and a greater number of family meals (B = −0.07, 95% CI −0.14 to −0.001, p = 0.048) were associated with lower NA.ConclusionOur results suggest a relationship between SEB and PA, while finding no association between family meals and PA, and an inverse relationship between both family meals and SEB with NA. Promoting positive social eating environments and family meals may be associated with adolescents’ emotional wellbeing.